Composition and functional diversity of soil and water microbial communities in the rice-crab symbiosis system. - Guo Yang; Tian Juncang; Wang Zhi (PLoS ONE)
Rice-crab co-culture is an environmentally friendly agricultural and aquaculture technology with high economic and ecological value. In order to clarify the structure and function of soil and water microbial communities in the rice-crab symbiosis system, the standard rice-crab field with a ring groove was used as the research object. High-throughput sequencing was performed with rice field water samples to analyze the species and abundance differences of soil bacteria and fungi. The results showed that the OTU richness and community diversity in soil were significantly higher than those in water, while there were significant differences in soil microbial diversity and OTU richness in water sediments. The dominant species at the bacterial phylum level were Amoebacteria, Cyanobacteria, Actinomycetes, Synechococcus and Greenbacteria, and at the genus level the dominant species were norank_f_norank_o_Chloroplast, unclassified_f_Rhodobacteraceae, LD29, Cyanobium_PCC-6307, and norank_f_MWH-UniP1_aquatic_group. The dominant species at the fungal phylum level are unclassified_k_Fungi, Ascomycota, Rozellomycota, Phaeomycota and Stenotrophomonas, and at the genus level the dominant species are unclassified_k_Fungi, unclassified_p_Rozellomycota, Metschnikowia, Cladosporium, unclassified_p_Chytridiomycota. The dominant phylum may rely on mechanisms such as organic matter catabolism, secretion of secondary metabolites and phototrophic autotrophy, as predicted by functional gene analysis. The main functional genes are related to metabolic functions, including secondary product metabolism, energy metabolism, and amino acid metabolism.